Management - Neck, Christopher P. (SAGE Publications, Inc. (US), 2024)
Management, Fourth Edition introduces students to the planning, organizing, leading, and controlling functions of management, with an emphasis on how managers can cultivate an entrepreneurial mindset. The text includes 34 case studies profiling a wide range of companies including The Progressive Corporation, Catch+Release, and Sephora. Authors Christopher P. Neck, Jeffery D. Houghton, and Emma L. Murray use a variety of examples, applications, and insights from real-world managers to help students develop the knowledge, mindset, and skills they need to succeed in today’s fast-paced, dynamic workplace.